Making plaque assessment easier – a validation study of simplified versions of the Marginal Plaque Index - Weik, Ulrike; Eidenhardt, Zdenka; Deinzer, Renate; Justus Liebig University Giessen (My University, 2024)
Background: The assessment of plaque indices may be time-consuming and error-prone. Simplification of these indices may increase their utility without compromising their validity. The aim of this study was to evaluate the validity of two simplified versions of the Marginal Plaque Index (MPI). Methods: Two simplified versions of the MPI as well as the Plaque Control Record (PCR) were derived from full-scale MPI assessments in two studies with four age groups (N = 42 10-year-olds; N = 24 15 year-olds; N = 53 university students (18y-33y); N = 66 parents (32y-57y). Correlations with the Turesky modification of the Quigley-Hein Index (TQHI) and the Papillary Bleeding Index (PBI) were calculated. Results: The indices derived from the MPI showed high convergence with each other (all r ≥ 0.94) and with the TQHI (r ≥ 0.80). The concurrent validity of the MPI with the PBI was equal to that of the TQHI in all age groups. The simplified versions of the MPI and the PCR show a lower convergent validity with the PBI than the MPI within parents (p < 0.05). In the other age groups, their convergent validity was equal to that of the MPI. Discussion: Simplification of the MPI does not affect its convergent validity with other plaque indices but may reduce its concurrent validity with the PBI in middle-aged adults.
Keywords: ddc:610